Conceptualization of resilience narratives of families of individuals with autism spectrum disorder - Sacdalan, Karen D. (College of Education, University of the Philippines Diliman, 2020)
This study examined the conceptualization of resilience found in the narratives of parents of individuals with Autism Spectrum Disorder (ASD). The crux of the narratives is the tensions, turning points, and areas of vulnerabilities felt by families during varies life stages. Ten families of various demographic background and experiences participated in this. Research data were gathered from parents, siblings, and children with ASD. Specifically, the narrative method of inquiry was employed to obtain information, which revealed a concept of resilience based on the contexts of the participants. It has been found that resilience is a sequential progression of the following: (1) acceptance, (2) Adjustment, and (3) advocacy. This lifespan model of resilience comes in varying degrees and intermittently present throughout the developmental lifespan of the child. Six components of resilience were found : (1) faith in God, (2) ASD knowledge, (3) family solidarity, (4) self-efficacy, (5) appropriate interventions, and (6) community support. The sequence of real-life problems, painful memories, and blissful recollections are the focal points that ushered new insights and life lessons of families of children with ASD. This study underscores the impact of disability, that through time, families created a unique perspectives towards child-rearing, career, lifestyle, social relationships, death, future aspirations, and other life concerns. In retrospect, the lived experiences of parents contained in the stories uncovered ways of seeing parenting role and the child with ASD.